Fabio Biondi, a conductor without baton Portrait of the Italian Conductor and Violinist (Télévision Suisse Romande, 2009)
Italian violinist and conductor, Fabio Biondi, is one of the most renowned musicians when it comes to performing Italian Baroque repertoires. From the beginning of his career, his attention focused specifically on the baroque violin and he would go on to work with many skilled conductors in ancient repertoires such as Marc Minkowski, Philippe Herreweghe and Jordi Savall. Since 1990 he has been playing in " Europa Galante", the orchestra he created, and which he conducts from his stand. Made up of fifteen musicians playing on period instruments, the group has been dedicated from the very beginning to the baroque Italian repertoire. His performances earned him an international reputation, and his 1991 recording of Vivaldi's The Four Seasons will go down in history. Fabio Biondi would not just be limited to scores from the past, but would extend his repertoire to the masterpieces of the Romantic era. As a protean artist, he would also be called upon to lead other formations including the Nice Opera, the Zurich Chamber Orchestra and the Mahler Chamber Orchestra. In this documentary, you will find him as a permanent guest conductor at the Lausanne Chamber Orchestra